A qualitative study on the effectiveness of training to job performance in KKR Microcredit Institution in Selangor - Sathyakumaran, Balasanthran (2018)
The purpose of this study is to examine the effectiveness of training to job performance among employees in the microcredit institutions, at KKR. This study employs the qualitative approach. Interviews were conducted with the employees of the KKR microcredit institutions. From the responses, it could be concluded that training in microcredit institutions had positive impact on employee’s job performance. However, in-depth interviews revealed that training in this microcredit institution was not planned systematically due to limited resource. Hence there is an opportunity for these microcredit institutions to plan systematic training programs for their employees.